Multiscale tetrahedral meshes for FEM simulations of esophageal injury - Neves, L. A. [UNESP]; Pavarino, E. [UNESP]; Souza, M. P. [UNESP]; Valencio, C. R. [UNESP]; Zafalon, G. F D [UNESP]; Nascimento, Marcelo Zanchetta Do; Tosta, Thaina (Institute of Electrical and Electronics Engineers (IEEE), 2015)
The radiofrequency cardiac ablation is a minimal invasive surgical procedure used for treating tachycardia, atrial fibrillation and atrial flutter. A possible complication is esophageal injury: The union of tissues from left atrium and esophagus, through necrosis. While this operation is being made, it is necessary to monitor the tissues temperatures accurately. The tests needed are complex and imply in death risks of the patient. Researchers are directed to simulate, with the finite element method, the behavior of the tissues under the influence of different levels of temperature: The objective is improving the cardiac ablation. Computational strategies were described in this work in order to obtain integrated meshes from thoracic and abdominal structures which are relevant to the study of this procedure. The methodology was based on strategies to represent structures in different scale and integrate software packages to generate meshes. The results were integrated, multiscale, and highly refined tetrahedral meshes from thoracic structures. The models were evaluated from dihedral angles histograms, indicating values between 5 and 170 degrees.
Keywords: cardiac ablation; modeling; multiscale; tetrahedral meshes; thoracic and abdominal structures